Sinergitas masyarakat kreatif dan perajin suling bambu terhadap pemberdayaan sumber daya alam (bambu bulo) di Kota Makassar - Aswar Aswar; Agussalim Djirong; Hasan Hasan (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This Community Partnership Program aims to synergize two competences in increasing purchasing power in markets and to correlate the competence the creative community (in this case is students majoring Visual Communication Design) on the utilization of natural resources integrated with business world (bamboo flute crafters). Based on the identification of problems and the potential of bamboo flute craftsmen in Tamalate district in Makassar, this program proposes several activities such as 1) increasing external competence of students through training in the business world in order to support the making of final assignments (produce packaging), 2) sharing competency between students and the business world in order to increase the selling value of bamboo flute through the producing of packaging and brochures as a promotional media. The results of this activity are a) training for classifying and manufacturing bamboo flutes with local materials for students. b) The implementation of producing packaging and brochure training for business community in Tamalate district of Makassar.